SELECTING RATED CAPACITY FOR POWER TRANSFORMERS - M. I. Fursanov; I. I. Dul (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2015)
The article proposes a method for selecting the rated capacity of oil-immersed power transformers adjusted for a more accurate calculation of their load-carrying capability. A more precise method to determine load-carrying capability of oil-immersed power transformers, which is admissible with valid technological normative documents, is offered and reasoned. The major attention focuses on the analysis of the requirements of the technological normative documents on selecting the rated capacity of oil-immersed power transformers. The authors present the critical analysis of the well-established and extremely simplified method for ratedcapacity selection of power transformers and justify its inconsistence.The paper shows that all the methods for selecting power-transformers rated capacity are the simplifications of the transformers load-capability assessment method based on thermal transient-processes computations. It is reasoned that the requirements of any transformer  operational-mode acceptability can be most precisely expressed in the form of critical-point allowable temperatures and the allowable overload-factors used in most applied methods are only indirectly calculated values. Allowable-temperature critical points regimented by the technological normative documents are cited.   The authors point to possible errors of the simplified selection-methods for rated capacity of oil-immersed transformers and adduce the computation results of the mathematical modeling of the thermal transient-processes under simplified conditions assumption to illustrate the  possible errors. The thermal transient-processes computation results for a transformer with   a 168-hour random electrical-load list demonstrate the performance capabilities of the offered  method.